Organization Capacity of Covid-19 Emergency Hospital Wisma Atlet Kemayoran in handling Covid-19 pandemic - Ruskar, Dandung; Yuli Subiakto; Bambang Wahyudi; I Dewa Ketut Kerta Widana (Technium Social Sciences Journal, 2022)
The prolonged pandemic causing the health worker deaths number in Indonesia became the highest in Asia and the top three worldwide. The organization’s capacity that is ready to be alert and responsive in anticipating and achieving bad possibilities becomes one of the determinants in the face of the highest Covid-19 patient surge at Covid-19 Emergency Hospital Wisma Atlet Kemayoran in July 2021. The national health crisis and the success of facing a surge in cases became the basis of researchers’ thinking to analyze the organization capacity at the Emergency Hospital Wisma Atlet Kemayoran. This research is qualitative research using descriptive analysis techniques using six elements of the organizational structure. The results of this study are: a) The specialization of health workers’ work is fulfilled through Health Registration Certificate qualifications, educational strata, and military strata; b) The organization has a strong command chain through the military role and the harmonization of military-civilian relations; c) The organization’s control range is adjusted based on service needs and supported by the availability of personnel based on Workload Analysis; d) Top manager decision-making is decentralized; e) Formalization of work is formed through rules and procedures, education and education and a safe work culture and f) Departmentalization of the organization in the form of lines and staff.